Possibilidades inclusivas do diálogo entre videntes e alunos com deficiência visual em uma sequência didática sobre Função Afim - Lorencini, Pricila Basilio Marçal (2019)
The inclusive ideology is based in the perspective of an education that is intended for all, in the right of all to learn together, without discrimination. This, in the first instance, implies legitimizing the differences, that is, not making them disappear, which does not mean, however, that the attendance of students with special educational needs should be individualized. An inclusive classroom seeks to overcome the difficulties arising from differences by offering inclusive activities that allow access to various learning groups, among which are the work in pairs of students. With these assumptions this research aimed to investigate the possibilities of learning for blind and low vision students with a didactic sequence involving the concept of Affine Function and its graphic representations. The implementation of the sequence was carried out by the researcher and the students solved in pairs having as main didactic orientation the description of the actions carried out using the natural language, in the oral and written modalities. The hypothesis of the research is that activities developed in this way can be carried out with the whole class, considering the inclusive perspective while allowing the blind student access to the information of visual appeals, which are not included in his textbook transcribed in braille. In addition, such activities enable all students, whether or not they see, to perform conversions from the graphic record to the natural language and vice versa, developing, according to Duval's theory, the learning of the concept in question. The description of strategies in the natural language enables students to present the knowledge mobilized in the predicative form, which is essential for learning, according to the Vergnaud Conceptual Fields theory. The activities of the didactic sequence (information gathering instrument) were elaborated considering conceptual aspects of the related function, in particular the basic ideas (variable, dependence, correspondence, regularity and generalization) and their different representations, and was presented in printed and transcribed forms in braille. In order to identify the learning of all students, analyzes of the audio recordings of the explicit knowledge (competences and conceptions, according to the Vergnaud Theory) concerning the Related Function were performed. The present research identified that the majority of students in this class of 2nd year of High School does not yet have the concept of Afim Function, because they predominantly mobilized, during the resolution of the didactic sequence, the indications of the operative and predicative forms of knowledge, in most cases in isolation. The basic ideas, of the Afim Function, more mobilized were: dependence, regularity, variable, correspondence. Regarding the idea of generalization, there is still a need for the teacher to take up and deepen this concept. As for the methodology, the students showed a good acceptance and affirmed that the work in pairs, besides favoring the exchange of ideas, promotes the respect to the differences, confirming the inclusive possibilities of the developed experience